Pengaruh Kebijakan Restrukturasi Pembiayaan Terhadap Stabilitas Perbankan Syariah di Indonesia: Bukti Empiris di Tengah Pandemi Covid 19 - Ahmad Fatoni (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to analyze the effect of financing restructuring policies through regulation No. 11/ POJK.03/2020 on Islamic banking stability in Indonesia. This study uses panel data from the 6 largest Islamic banking in Indonesia for the period September 2018 to December 2020. This study uses the REM model as the best estimation model. The results showed that the financing restructuring policy had a negative and significant effect on the stability of Islamic banking ini Indonesia. Meanwhile, Non-Performing Financing (NPF) and Gross Domestic Product (GDP) as control variables have a possitive significant effect on Islamic banking stability. Meanwhile, inflation has a negative and significant effect on the stability of Islamic banking. This study did not find the effect of bank size on the stability of Islamic banking in Indonesia.